The Impact of Upin and Ipin TV Series on Social Behavior Changes of 4-5 years-old Children in Bandung City - Meilia Azzahra, Sandra; Wiryany, Detya; Nuradina, Kartika (International Journal of Psychology and Health Science, 2024)
The Preschool phase in a child's life is a crucial period requiring heightened supervision. The formation of a child's behavior is heavily influenced by parental, teacher, and environmental education, encompassing their daily observations. The Upin and Ipin animated film serves as a conduit for children to imbibe values like respect, affection, cooperation, appreciation for religious diversity, worship practices, and cultural understanding. This cinematic experience positively enriches children's understanding of virtuous behavior, given their natural inclination to emulate observed actions psychologically. The research aims to ascertain the influence of Upin and Ipin shows on behavioral changes and knowledge development in children. Employing a qualitative descriptive approach, the study involves children who are avid viewers of Upin and Ipin, utilizing instruments such as interviews and observations. The data analysis encompasses reduction, concluding, and verification steps. Findings reveal the Upin and Ipin animated film has a favorable impact on children, fostering behavioral transformations, enhancing their grasp of etiquette in parental interactions, and inspiring language emulation, all while fostering knowledge acquisition across various disciplines presented in the show.